2004
DOI: 10.1074/jbc.m402016200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Application Probes a Novel and Ubiquitous Family of Enzymes That Alter Monosaccharide Configuration

Abstract: By exploiting nuclear magnetic resonance (NMR) techniques along with novel applications of saturation difference analysis, we deciphered the functions of the previously uncharacterized products of three bacterial genes, rbsD, fucU, and yiiL, which are part of the ribose, fucose, and rhamnose operons of Escherichia coli, respectively. We show that RbsD catalyzes the pyran to furan conversion of ribose, whereas FucU and YiiL are involved in the catalysis of the anomeric conversion of their respective sugars. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 23 publications
1
43
0
1
Order By: Relevance
“…Mutarotases facilitate the interconversion of ␣ and ␤ anomers where the stereochemically less-favored anomer is required for a subsequent step in a catabolic sequence. Three such examples have so far been identified, including L-rhamnose mutarotase (YiiL in E. coli) (30, 31), galactose mutarotase (GalM) (5,6,8,9,14,36,37,38,39), and fucose mutarotase (FucU) (16,30). In this report, we characterize rhaU from R. leguminosarum and provide evidence that is consistent with the hypothesis that RhaU is an L-rhamnose mutarotase.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Mutarotases facilitate the interconversion of ␣ and ␤ anomers where the stereochemically less-favored anomer is required for a subsequent step in a catabolic sequence. Three such examples have so far been identified, including L-rhamnose mutarotase (YiiL in E. coli) (30, 31), galactose mutarotase (GalM) (5,6,8,9,14,36,37,38,39), and fucose mutarotase (FucU) (16,30). In this report, we characterize rhaU from R. leguminosarum and provide evidence that is consistent with the hypothesis that RhaU is an L-rhamnose mutarotase.…”
supporting
confidence: 72%
“…Sequence similarity (41% identity) suggested that RhaU was related to a group of hypothetical proteins that included YiiL of E. coli (28), which was recently characterized as an L-rhamnose mutarotase, catalyzing the ␣-to ␤-anomeric conversion of L-rhamnose (30,31). Based on the phenotype produced by yiiL in E. coli, it was expected that a rhaU-containing mutant would grow normally at high concentrations of L-rhamnose (0.2%) and more slowly at low concentrations (0.03%), but Rlt243 exhibited a slow-growth phenotype even at high L-rhamnose concentrations ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study (13), it was shown that the RbsD protein was required for growth on ribose when the sugar was transported through a mutated glucose transporter (PtsG). Recently, RbsD was characterized as a novel type of mutarotase involved in the anomeric conversion of ribose (16). Here, we report a growth inhibition phenotype of RbsD when the rbsD and rbsACBK genes were overproduced on separate plasmids (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…This is particularly evident in cells transporting ribose at a lower affinity (13). It was found that monosaccharide mutarotases, including RbsD, are ubiquitous and conserved in both prokaryotes and eukaryotes (16). Intracellular production of MG is achieved in E. coli and most bacteria by MG synthase encoded by the mgs gene (20).…”
mentioning
confidence: 99%
“…This was confirmed by the STD spectra recorded for these three sugars (data not shown). Second, enzyme catalyzed anomeric interconversion was investigated using two- (32). Exchange cross-peaks between ␣ and ␤ Glc6P anomers could only be observed in the presence of YMR099cp enzyme (Fig.…”
mentioning
confidence: 99%